‘Power-sharing government mechanisms' : are they a solution or an obstacle to democratisation in Africa? A focus on South Africa and Zimbabwe - Michel, Didier Jean Benoit (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.